2019
DOI: 10.1016/j.sdentj.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution & deflection in an Aramany class II obturator fabricated with cobalt-chromium & titanium alloys – 3D FEA

Abstract: Purpose/objectivesThe aim of the research was to develop a model that accurately represents an Aramany class II defect and its obturator prostheses fabricated with Cobalt Chromium alloy & Titanium alloy to compare the deflection and the stress distribution in the rehabilitated area.MethodsAramany class II defect and the obturator prostheses was generated geometrically utilizing ANSYS 14.5, both overlaid on each other to impressionist prostheses and the maxilla as one element. Meshing of models was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…One of them evaluated the stress in congenitally unilateral palatal cleft scenario [25], one used mainly in vivo approach with no interpretation in the result and discussion sections regarding FEA [23], and four different studies were duplicated in their methodology and results [24,26], so we chose the earlier studies [13,27]. Finally, 13 articles were recruited for this review [13,[27][28][29][30][31][32][33][34][35][36][37][38]. The number of primary surveyed articles, number of excluded articles, reasons for exclusion, and the final recruited articles are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One of them evaluated the stress in congenitally unilateral palatal cleft scenario [25], one used mainly in vivo approach with no interpretation in the result and discussion sections regarding FEA [23], and four different studies were duplicated in their methodology and results [24,26], so we chose the earlier studies [13,27]. Finally, 13 articles were recruited for this review [13,[27][28][29][30][31][32][33][34][35][36][37][38]. The number of primary surveyed articles, number of excluded articles, reasons for exclusion, and the final recruited articles are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies that evaluated dentulous scenarios of Aramany's class I and class II palatal defect, they found that the maximum stress concentration is located around the cervical half of the roots of the teeth next to the resection, central, and lateral incisors of the contralateral side in class I or canine in [13,30,35]. The cobalt-chromium alloy was found to produce more stress on the remaining teeth, when used as a major connector and retainers, compared to titanium alloy which showed more flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations